PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Permatasari, Felia; Widianingsih, Luky Patricia (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
The purpose of this studies is to know how the influence of CSRdisclosure on financial performance with GCG as a moderating variable.CSR disclosure is measured using CSRD Index based on GRI G4. The dependentvariable of this study is financial performance which is proxied byreturn on assets and return on equity. The GCG moderation variable isproxied by institutional ownership, the size of the board of commissionersand the independent board of commissioners. The sample used in this studyis a SOE’s company non-financial listed on the Indonesia Stock Exchangein the period 2014–2018. The results of this studies found that CSR disclosurehas a positive effect on financial performance (ROA) and CSR disclosurehas no effect on financial performance (ROE). GCG variables whichare proxied by institutional ownership is not able to moderate the effect ofCSR on financial performance (ROA and ROE), the size of the board ofcommissioners able to strengthen the effect of CSR on financial performance(ROA) and independent board of commissioners is not able to strengthenthe effect of CSR on financial performance (ROA), the size of the board ofcommissioners and independent board of commissioners is not able to moderatethe effect of CSR on financial performance (ROE).